Psychodynamics, training, and outcome in brief psychotherapy - Malan, David H. (David Huntingford) (Butterworth-Heinemann, 1992)
Psychodynamics, Training, and Outcome in Brief Psychotherapy provides information pertinent to the fundamental aspects of dynamic psychotherapy. This book discusses the selection criteria, the principles of therapeutic methods, and the factors leading to therapeutic effects in psychotherapy.